Dialogue and materiality/embodiment in science|arts creative pedagogy: Their role and manifestation. (March 2019) - Chappell, K.; Hetherington, L.; Keene, H. Ruck; Wren, H.; Alexopoulos, A.; Ben-Horin, O.; Nikolopoulos, K.; Robberstad, J.; Sotiriou, S.; Bogner, F.X.
Highlights: New fusion of Bakhtinian-inspired and New-Materialist understandings of dialogue emphasising embodiment to revitalise how we articulate dialogue. Matter as well as meaning is constituted in the dialogic space of science|arts creative pedagogy. This leads to new assemblages of embodied teachers, students, ideas, and objects. Diffractive analysis offers benefits: fore-fronting entangled relationality, avoiding bracketing side-lined educational elements; opening out pedagogical approaches and challenging what education is for. Opening up new ways for teachers, students and researchers to experience seeing, doing, feeling and researching science|arts creative pedagogy. Abstract: This paper responds to recent calls to explore the nuances of the interaction between the sciences, the arts and their inherent creativity to better understand their potential within teaching and learning. Building on previous arguments that the science-arts-creativity relationship is dialogic and relational, this research focuses on the question: How are dialogue and material/embodied activity manifested within creative pedagogy? We begin with a fusion of Bakhtinian-inspired and New-Materialist understandings of dialogue drawing out the importance of embodiment in order to revitalize how we articulate dialogue within creative educational practice. We then take on the challenge of a materialist diffractive analysis to conduct research which complements the theoretical framing and offers our outcomes in a way that appropriately makes the phenomena tangible. We present the outcomes of the diffractive analysis including the constitution of matter as well as meaning in the dialogic space; and the emergence of new assemblages of embodied teachers, students, ideas, and objects within transdisciplinary educational practice. We conclude by arguing for the benefits of diffractive analysis: that we have fore-fronted the entangled relationality of trans-disciplinary creative pedagogy; avoided bracketing out aspects of education that are often side-lined; opened out the space of pedagogical approaches that might be attempted; and begun to challenge what education is for. In so doing, the article aims to open up new ways for teachers, students and researchers to experience seeing, doing, feeling and researching science|arts creative pedagogy and provoke conversations about how this might develop in the future.